2017
DOI: 10.31436/imjm.v16i1.362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flaxseed Extract on the Liver Histological Structure in Streptozotocin Induced Diabetic Rats

Abstract: Introduction: Diabetes mellitus has become a serious warning to mankind health all over the world. The management goal of diabetes is to keep blood glucose levels as close as possible to healthy individuals. Medications used to treat diabetes are usually associated with complications and may cause different side effects. Many traditional anti-diabetic plants have become popular in the management of diabetes mellitus. Flaxseed has been used as traditional medicine for centuries. Objective: This study aimed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The treatment groups of 0.25 and 1 mg/kg hUC-MSCs-sEVs and glibenclamide had restored normal liver architecture with no specific pathology or inflammation compared to untreated diabetic rats. This finding agrees with a previous study by Al-ani et al [ 26 ], who found glibenclamide-treated STZ-induced diabetic rats showed fewer pathological changes to liver architecture, indicating a protective effect of the treatment against hepatic changes associated with diabetes. In addition, the finding is supported by Diaz-Juarez et al [ 27 ], who found that elevated hepatic enzymes did not correlate with cell necrosis.…”
Section: Discussionsupporting
confidence: 93%
“…The treatment groups of 0.25 and 1 mg/kg hUC-MSCs-sEVs and glibenclamide had restored normal liver architecture with no specific pathology or inflammation compared to untreated diabetic rats. This finding agrees with a previous study by Al-ani et al [ 26 ], who found glibenclamide-treated STZ-induced diabetic rats showed fewer pathological changes to liver architecture, indicating a protective effect of the treatment against hepatic changes associated with diabetes. In addition, the finding is supported by Diaz-Juarez et al [ 27 ], who found that elevated hepatic enzymes did not correlate with cell necrosis.…”
Section: Discussionsupporting
confidence: 93%
“…The liver plays a pivotal role in glucose and lipid homeostasis, is severely affected by diabetes [34]. Al-Ani et al [35] reported the presence of morphological and histological alterations in liver tissues of rats treated with alloxan, as indicated by the increase in liver weight, glycogen reduction, associated with lipid deposition, inflammatory cells infiltration and Kupffer cells hyperplasia. It has been previously reported that alloxan causes central venous congestion with significant dilatation of the sinusoidal spaces of liver tissue [36].…”
Section: Discussionmentioning
confidence: 99%